2019
DOI: 10.1101/533968
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Community-based Sero-prevalence of Hepatitis B and C Infections in South Omo Zone, Southern Ethiopia

Abstract: 16Background: Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) are the leading causes of 17 liver-related morbidity and mortality throughout the world. The magnitude of HBV and HCV 18 infections in Ethiopia has not been well studied at community level. This study aimed at 19 investigating the sero-prevalence and associated risk factors of HBV and HCV among HBV 20 unvaccinated community members in South Omo Zone, Southern Ethiopia. 21 Methods: A community-based cross-sectional study was conducted in … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 33 publications
2
4
0
Order By: Relevance
“…Overall anti-HCV seroprevalence was 1.9% (95% CI: 0.9%, 3.0%), which is considered low endemicity by WHO. 22 , 23 The results were consistent with the results of the previous studies conducted on the general population in the South Omo Zone, 1.9%, 20 the recent pooled national prevalence of 2%, 34 the 2% prevalence reported from Gambella, Ethiopia 18 and 1.4% among community members in southern Ethiopia 19 However, the seroprevalence was less than that of 3.1% of the previous national pooled prevalence, 17 4.3% in previous studies reported from Northwest Ethiopia, 35 3.0% prevalence found in sub-Saharan Africa, 36 , 37 3.4% Africa, 4.8% Somalia, 6.2% Pakistan, 6.5% Cameron, and 11.9% Egypt. 38–42 On the contrary, it is greater than the 1.0% prevalence reported in Gojjam, Ethiopia; 28 0.64% prevalence reported in Nekemite, Ethiopia, 43 0.4% in Iraq, 44 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan 36 among the general populations.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Overall anti-HCV seroprevalence was 1.9% (95% CI: 0.9%, 3.0%), which is considered low endemicity by WHO. 22 , 23 The results were consistent with the results of the previous studies conducted on the general population in the South Omo Zone, 1.9%, 20 the recent pooled national prevalence of 2%, 34 the 2% prevalence reported from Gambella, Ethiopia 18 and 1.4% among community members in southern Ethiopia 19 However, the seroprevalence was less than that of 3.1% of the previous national pooled prevalence, 17 4.3% in previous studies reported from Northwest Ethiopia, 35 3.0% prevalence found in sub-Saharan Africa, 36 , 37 3.4% Africa, 4.8% Somalia, 6.2% Pakistan, 6.5% Cameron, and 11.9% Egypt. 38–42 On the contrary, it is greater than the 1.0% prevalence reported in Gojjam, Ethiopia; 28 0.64% prevalence reported in Nekemite, Ethiopia, 43 0.4% in Iraq, 44 0.3% in Djibouti, 0.9% in Somalia, and 1.0% in Sudan 36 among the general populations.…”
Section: Discussionsupporting
confidence: 91%
“… 45–48 In current study, coinfection was 0.3% among the general population in the community of Wolaita. This was in line with 0.3% prevalence among community members in South Omo Zone, 20 0.2% prevalence in Hawassa University Comprehensive Specialized Hospital, Hawassa City, Southern Ethiopia, 49 0.4% prevalence among hemodialysis patients in Addis Ababa, Ethiopia 50 and 0.43% prevalence among surgical patients in Lahore. 51 HBV seroprevalence was determined by using viral antigen (HBsAg) as a serologic marker, and HCV infection by antibody (anti-HCV antibody), both confirmed by ELISA.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Available studies are clinic-based and represent different subpopulations. Two general population-based studies in northwest (2015) 10 and southern (2018) 11 Ethiopia found the prevalence of HCV infection to be 1.0% and 1.9%, respectively. The prevalence of HCV infection in blood donors ranges from 0.3% 2 to 1.3%, 12 with wider variations among different cities.…”
Section: Resultsmentioning
confidence: 99%